Thermal management of a battery pack using a layer of phase change material around the batteries: Changes in the airflow through the battery. (1st August 2022) - Ajour, Mohammed N.; Milyani, Ahmad H.; Abu-Hamdeh, Nidal H.; AlQemlas, Turki; Khaled, Moath K.; Karimipour, Arash
Abstract: In this paper, a battery pack with 27 lithium-ion cylinder batteries is simulated in two dimensions. This consists of 3 rows of 9 batteries. All batteries are made of phase change material, which is placed in a circular chamber. There is airflow at the Reynolds number ranging from 100 to 400. Temperature, airflow, the volume percent of molten phase change material, the highest and average temperatures of the battery pack, ambient air temperature, and volume fraction are all measured from 0 to 3000 s in this research. COMSOL Multiphysics 5.4 software is used for numerical analysis. The results demonstrate that the ambient air temperature at Reynolds number = 100 does not control the temperature of the battery and its temperature has an increasing trend. Also, the temperature of the output air from the battery pack is reduced with the Reynolds number. At 3000 s, the molten phase change material at Reynolds number = 400 is 30.74% lower than that at Reynolds number = 100. At all values of Reynolds number, enhancing the time reduces the amount of molten phase change material. Highlights: Simulation the 2-dimensional battery pack with 27 lithium-ion cylinder batteries The effects of changes in the airflow through the battery pack Battery pack thermal management using a layer of phase change material